PENGARUH PENGETAHUAN PERPAJAKAN, SOSIALISASI PERPAJAKAN, PENERAPAN SISTEM E-FILING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI MASA PANDEMI COVID-19 - Tasum Tasum (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
The purpose of this study was to determine the effect of the variable knowledge of taxation, tax socialization, and the application of the e-filing system on individual taxpayer compliance during the Covid-19 pandemic. This research uses associative quantitative method using a questionnaire with a semantic differential measurement scale. This research was conducted on individual taxpayers who are registered as mandatory SPT and have NPWP at KPP Pratama Pondok Gede.